HOMOLOGI FUNGSI GEN KNAT1 ( Knotted 1– like Arabidopsis thaliana) PADA ANGGREK BULAN Phalaenopsis amabilis (L.) Bl. DENGAN MEDIATOR Agrobacterium tumefaciens - Sulastri Isminingsih; Endang Semiarti; Aziz Purwantoro (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2009)
ABSTRACTTo understand the function of KNAT1 gene Arabidopsis in the forming and developing of Indonesian origin orchid shoot Phalaenopsis amabilis through transform p35S::KNAT1 and pGreen to protocorm like bodies (plb) of the orchid mediated by Agrobacterium tumafaciens LBA4404. The plb transformants were grown on New Phalaenopsis selection medium containing 5 mg/l BAP, 0.15 mg/l NAA, 15 mg.l Kanamycin and addition of 300 mg/l Cefotaxim to eliminate the overgrowth of Agrobacterium. The analysis of positive transformant use Polimerase Chain Reaction (PCR) with the specific oligonucleotide primers for KNAT1 gene: KNAT1F1R1 and universal primers for pGreen: 35SO and Tnos. The result shows that 3 shoots of 1850 transformants positively carry out the 35S::KNAT1 construct (frequency of transformation was 0.16 %) while 5 shoot of 1850 transformants also positively carry out the pGreen vector, with the frequency of transformation was 0.27 %. The phenotype analysis of 35S::KNAT1 transformants show multiplication on forming of the leaf from a plb to + 10 shoots and forming of the leaf shape which has terompet like shapes and rectangular shape.Key words: Arabidopsis, KNAT1 gene, Phalaenopsis amabilis, shoot